Students' motivation towards learning electronics and its relationship to academic achievement at the Technical Institute of Kalar - Kurdistan Hamid Muhammad (The Scientific Journal of Cihan University– Sulaimaniya, 2018)
The study aimed to identify the motivation towards the learning electronic subjects and its relationship to the academic Achievement Among Students of Kalar Technical Institute. The researcher used the descriptive analytical method, and a questionnaire as a tool for the study, which consisted of (23) items, and applied to a sample of (84) students from electricity department at the Technical Institute of Kalar in academic year(2016/2017) followed by the confirmation of the validity and reliability. After the collecting of data analysis by researcher used(SPSS), the study found: the motivation of students sample to learn the electronic subjects was positively moderate, and no statistically significant difference in the level(α =0.05) between the motivation of study sample members about learning electronic subjects due to the effect of the gender of the students in favor of female students, as well as found positive correlation between the motivation of students' relationship and academic achievement(practical and theoretical subjects of electronic). In the light of the findings, the study found a related number of recommendations and suggestions.